Pemantauan Kualitas Air Sungai Digoel, Distrik Jair, Kabupaten Boven Digoel, Papua - Rosye H.R. Tanjung; Hendra K. Maury; Suwito Suwito (Jurusan Biologi FMIPA Universitas Cenderawasih, 2016)
Digoel river have an important role to the human activity and environment in Boven Digoel Regency. Increasing of human and industrial activity around the watershed of Digoel River were suspecious to cause the degradation water quality in Digoel River. This research was done to monitor the impact of the industrial activity to the quality of water in outlet of waste water treatment plant(WWTP) of PT. Korindo to the water quality of Digoel River. Parameter analised are the physical, chemical, organic chemical, microbiology and metal content in water. Analysis of the water quality accordance to PP Nomor 82 Tahun 2001 about water quality managementand water pollution and Permen LH Nomor 5 tahun 2014 about the quality of waste water.The monitoring was conducted in three months at five sampling stasion (river upstream, river down stream, outlet WWTP plywood, outlet WWT workshop, outlet WWTP palm oil) in Districk Jair. The rsult showed, parameter of BOD, COD, phospate, phenol and total coliform in Digoel River exceeded class I of water quality standards. Outlet of plywood WWTP have two parameters that exceed the quality standard which were TSS 15.67 mg/L and phenol 13.33 mg/L.The outlet of WWTP workshop have four pameter exceeded the quality standard which were TSS (383.67 mg/L), oil/fats (502.0 µg/L), phenol (11.0 µg/L), and zinc (21,000 mg/L). IPAL oil WWTP outlet have two parameter sexceeded the quality standars which were oil/fats (313.0 µg/L) and total coliform (> 979 cells/100 mL). The result indicating that the status of water quality of Digoel River are categorized as “lightly polluted”. Therefore based on utilization, it was categorized as class IV water quality that can be used for irrigating, planting and other purposed that meet the requairement of water qualiy in this class, while for other uses need necessary processing. In order not to increase the pollution in the Digoel river the WWTP of industry around Digoel River should improved their treatment, so that waste water discharged to the Digoel River not exceed the stanards quality.Key words: water quality, digoel river, status of water quality, pollutant index.